Creatinine clearance in selection of living kidney donor among the Malaysian population: is it safe? - Chee Keong Thye; Yee Wan Lee; Maisarah Jalalonmuhali; Soo Kun Lim; Kok Peng Ng (BMC Nephrology, 2023)
Abstract Background Assessment of donor renal function is made by the measurement of Glomerular Filtration Rate (GFR). Exogenous markers are preferred over creatinine clearance and are widely used for measuring GFR. However, they are difficult to obtain, costly and laborious. This is a study to look into the safety and accuracy of creatinine clearance for renal assessment among the living kidney donors in the Malaysian population. Methods This is a retrospective, single-centre study comprising 105 living kidney donor candidates from the year 2007 to 2020. By comparing against 51-Chromium ethylenediamine-tetraacetic acid (51Cr-EDTA), we analysed creatinine clearance for correlation, bias, precision and accuracy. Results The study group had a mean age of 45.68 ± 10.97 years with a mean serum creatinine of 64.43 ± 17.68 µmol/L and a urine volume of 2.06 ± 0.83 L. Mean measured GFR from 51Cr-EDTA was 124.37 ± 26.83 ml/min/1.73m2 whereas mean creatinine clearance was 132.35 ± 38.18 ml/min/1.73m2. Creatinine clearance overestimated 51Cr-EDTA significantly with a correlation coefficient of 0.48 (p < 0.001) and an accuracy of 78.10% and 64.0% within 30% and 20% respectively of 51Cr-EDTA. Conclusion Creatinine clearance is an acceptable and affordable alternative for donor renal assessment in the absence of exogenous markers with an emphasis on adequate urine collection followed by using measured GFR in selected cases.